2022
DOI: 10.1002/car.2785
|View full text |Cite
|
Sign up to set email alerts
|

False Controversy Regarding Abusive Head Trauma Endangers Vulnerable Children

Abstract: The diagnosis of AHT is not a controversial one, and the principal mechanism of AHT is shaking.• Absence of circular reasoning in diagnosing AHT has been confirmed by recent research that demonstrated clear differences between witnessed/admitted AHT and witnessed accidental head trauma. • False controversy regarding AHT and the flawed arguments used to sustain it should be ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This re-analysis found that crying remained the most common trigger, accounting for 51 per cent of cases, with revival attempts accounting for 37 per cent of cases and anger or frustration 12 per cent of cases. Edwards et al (2022) offer a firm rebuttal of this critique also published in this issue. They argue that the diagnosis of AHT is not a medically controversial one and that the principal mechanism of AHT is shaking, as demonstrated across multiple countries involving various models of jurisprudence.…”
Section: Abusive Head Traumamentioning
confidence: 80%
See 3 more Smart Citations
“…This re-analysis found that crying remained the most common trigger, accounting for 51 per cent of cases, with revival attempts accounting for 37 per cent of cases and anger or frustration 12 per cent of cases. Edwards et al (2022) offer a firm rebuttal of this critique also published in this issue. They argue that the diagnosis of AHT is not a medically controversial one and that the principal mechanism of AHT is shaking, as demonstrated across multiple countries involving various models of jurisprudence.…”
Section: Abusive Head Traumamentioning
confidence: 80%
“…Edwards et al (2022) offer a firm rebuttal of this critique also published in this issue. They argue that the diagnosis of AHT is not a medically controversial one and that the principal mechanism of AHT is shaking, as demonstrated across multiple countries involving various models of jurisprudence.…”
Section: Abusive Head Traumamentioning
confidence: 88%
See 2 more Smart Citations